ANTIBACTERIAL ACTIVITIES AND CHEMICAL COMPOSITION OF ESSENTIAL OIL OF BLUMEA BALSAMIFERA (L.) DC., DISTRIBUTED IN LAMDONG PROVINCE, VIETNAM - Hoàng Thị Bình; Nguyễn Minh Trí; Nguyễn Hữu Quân; Nguyễn Văn Ngọc (Tạp chí Khoa học Đại học Đà Lạt)
In the present study, the chemical composition and the antibacterial properties of the essential oil obtained from fresh leaves of Blumea balsamifera (L.) DC. in Lamdong are reported. The hydrodistillation method was used to isolate essential oil from leaves of this species, and gas chromatography/mass spectrometry (GC-MS) techniques were used to analyze the chemical constituents of the essential oil. Thirty six chemical constituents of the essential oil derived from fresh leaves of B. balsamifera were identified, in which the major compounds of the essential oil were camphor, caryophyllene, caryophyllene oxide, β-eudesmol, thymol hydroquinone dimethyl ether, and t-eudesmol, accounting for 43.69%, 12.71%, 5.98%, 4.84%, 4.63%, and 3.32%, respectively. Moreover, by using the agar well diffusion method, the antibacterial effects of B. balsamifera essential oilagainst Staphylococcus aureus and Escherichia coli were tested by the inhibition zone diameter test to evaluate the antibacterial activity.